Design of prestressed concrete - Nilson, Arthur H., Prof. (John Wiley and Sons, 1987)
Design of prestressed concrete; Basic concepts; Materials; Flexural analysis & design; Shear & torsion; Beams and frames-composite & continuous; Deflections; Slabs; Axially loaded members; Precast construction; Applications.